The Mediating Role of Job Satisfaction and Family-Supportive Supervisor Behavior in the Relationship Between Work–Life Balance and Job Performance Among Generation Z Employees - Muna Inayah; Alex Winarno; Anita Silvianita (Digital Innovation : International Journal of Management, 2026)
This study explores the impact of work–life balance on job performance among Generation Z employees in Jakarta, with job satisfaction as a mediating variable and family-supportive supervisor behavior as a moderating variable. Generation Z, the largest segment of Indonesia's workforce, values flexibility and supportive leadership, but their job performance often shows inconsistency. Previous studies have yielded mixed results on the relationships between work–life balance, job satisfaction, and job performance, with limited empirical evidence on the role of family-supportive supervisor behavior, particularly in Indonesia. Using a quantitative approach, data were collected from 385 Generation Z employees in Jakarta through purposive sampling. Structural Equation Modeling (SEM) with SmartPLS 4.0 was used for data analysis. Results indicate that work–life balance positively influences both job satisfaction and job performance. Additionally, job satisfaction partially mediates the relationship between work–life balance and job performance, suggesting that a better work–life balance enhances job satisfaction, which in turn improves performance. The study also shows that family-supportive supervisor behavior significantly strengthens the positive effect of work–life balance on job performance. These findings contribute to the literature by clarifying how work–life balance affects job performance among Generation Z employees and highlighting the importance of supportive leadership.